Enjoy Poverty - Martens, Renzo (The Netherlands, 2009)
"Enjoy Poverty" is a film registration of Martens' activities in the Congo. In an epic journey, the film establishes that images of poverty are the Congo’s most lucrative export, generating more revenue than traditional exports like gold, diamonds, or cocoa. However, just as with these traditional exports, those that provide the raw material: the poor being filmed, hardly benefit from it at all.
Verzio Film Festival Submission
Keywords: Documentary films